Teacher Efficacy, Work Engagement, and Social Support Among Chinese Special Education School Teachers - Minghui, Lu; Lei, Hao; Xiaomeng, Chen; Potměšilc, Miloň (Frontiers in Psychology, 2018)
This paper investigates the relationship between teacher efficacy and socio-demographic factors, work engagement, and social support among Chinese special education school teachers. The sample comprised 1,027 special education school teachers in mainland China. The Teachers’ Sense of Efficacy Scale (TSES), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Utrecht Work Engagement Scale (UWES) were used for data collection. Correlation analysis revealed that social support, work engagement, and teacher efficacy were significantly correlated with each other. Additionally, gender, years of experience, and monthly salary were significant predictors of teacher efficacy. Furthermore, structural equation modeling (SEM) analysis showed that social support exerted its indirect effect on teacher efficacy through the mediation of work engagement. These findings provide a new perspective on the complex association between social support and teacher efficacy. Possible explanations for these findings and the limitations of this research are discussed.